2021
DOI: 10.1177/07482337211042731
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of blood lead among painters of buildings and cars

Abstract: Exposure to lead-based paints is a major threat to the health of painters. This study aimed to evaluate the blood concentration of lead (Pb) in painters of buildings and cars. The present study was a cross-sectional study in which a semi-structured questionnaire was used to collect the socio-demographic information. Lead concentration in blood samples was determined using the atomic absorption spectrometry method. A total of 32 male painters were selected based on inclusion criteria. The mean blood lead level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A similar study reported that in Nigeria, the level of operation time was associated and significant increasing of blood lead level on automobile mechanics [9] . In the same way, studies that were conducted in Jimma, Ethiopia, and Iran found that the exposure of blood lead level had a direct relationship to extra working hours [2,30] . It could be explained that extra working hours and long duration of service years were important factors to occupational lead exposure.…”
Section: Factors Associated With Blood Lead Level Of the Study Partic...mentioning
confidence: 71%
See 1 more Smart Citation
“…A similar study reported that in Nigeria, the level of operation time was associated and significant increasing of blood lead level on automobile mechanics [9] . In the same way, studies that were conducted in Jimma, Ethiopia, and Iran found that the exposure of blood lead level had a direct relationship to extra working hours [2,30] . It could be explained that extra working hours and long duration of service years were important factors to occupational lead exposure.…”
Section: Factors Associated With Blood Lead Level Of the Study Partic...mentioning
confidence: 71%
“…One of the most unnecessary and harmful substances for public health concerns about occupational chemical exposures that occurred at automotive garage sites was lead. Lead is one of the heavy metals commonly observed as an occupational hazard for workers who are working in car painting, welding, maintenance, mechanics, and electricians [1,2]. Hence, garage workers are more exposed to heavy metals, especially lead, than the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Although lead can enter the water supply from a variety of sources, including old lead pipes, plumbing fixtures, lead solder used in plumbing, and lead-containing valves or fittings, the municipality water supply was found to have lead within permissible limits. The present study results were comparable to those of recent studies: a meta-analysis of 31 studies involving the Indian population, i.e., 5472 people across nine states, reported a mean BLL of 7.52 µg/dL (95% CI: 5.28 -9.76) in non-occupationally exposed adults [18]; a cross-sectional study of 32 male painters in Iran in 2021 reported a mean BLL of 8.1 ± 4.93 µg/dL [19]; a cross-sectional study among 254 workers aged 20 -60 years old, at a battery factory in Nellore, Andhra Pradesh, in 2016 -17 reported a mean BLL of 25.26 ± 2.1 µg/dL 3 ; and a study from Turkey in 2001 among 99 traffic policemen reported a mean BLL of 9.4 ± 1.6 µg/L and 8.7 ± 1.7 µg/L for policemen working outdoors and indoors, respectively [20]. Our results were also lower compared to a study from China [21].…”
Section: Discussionmentioning
confidence: 84%
“…A similar study reported that in Nigeria, the operation time was associated with a significant increase in blood lead levels according to automobile mechanics [ 9 ]. Similarly, studies conducted in Jimma, Ethiopia, and Iran have shown that exposure to blood lead has a direct relationship with additional working hours [ 2 , 31 ]. This could be explained by the fact that extra working hours and a long duration of service were important factors in occupational lead exposure.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most nonessential and harmful types of heavy metals for public health concerns that is still found in occupational work and the environment is lead. Lead is commonly observed as an occupational hazard for workers who are working in painting, welding, battery maintenance, mechanics, and electricity [ 1 , 2 ]. Garage workers are more exposed to lead than non-garage workers.…”
Section: Introductionmentioning
confidence: 99%